Pomegranate Peel extract in Edible films: Impact on Microbial Growth Oxidative Stability, and Sensory Quality of Beef - Shokhan Hidayat Hamarashid; Nehan Bahaaldeen Jafar; Naska Abdulqadr Muhamad (University of Thi-Qar Journal of agricultural research, 2025)
This study assessed the antimicrobial, antioxidant and organoleptic effects of pomegranate peel powder (POP) incorporated into sodium alginate films and the mechanical and chemical properties of films enriched with pomegranate peel extract (PPE). Bovine samples were coated with films containing 0% (control), 2.5%, 5%, 7.5% and10% POP, and their quality was analyzed during 14 days of refrigerated storage. Microbial counts, including the aerobic plate count (APC), psychrotrophic count (PTC), and Enterobacteriaceae count (EC), significantly decreased with increasing POP concentrations. The 10% POP (Pop4) treatment demonstrated robust antimicrobial activity, maintaining APC at 3.503 log CFU/g compared to 7.630 log CFU/g in the control by day 14. Oxidative stability was significantly improved, with peroxide value (PV) and thiobarbituric acid reactive substance (TBA) levels in Pop4 reduced by 53.6% and 76.7%, respectively, compared to the control. Sensory analysis indicated superior preservation of color, odor, and overall acceptability in POP-treated samples. Concurrently, films enriched with PPE exhibit enhanced mechanical and barrier properties. Increased PPE concentrations improved film thickness (0.062 mm in T4, 10% PPE), tensile strength (46.450 MPa in T4), and water vapor barrier properties (0.005–0.007 g/m² over 24 h), while reducing moisture content and enhancing elongation at break (4.57% in T4 compared to 3.11% in control films). These findings indicate that edible films enriched with POP and PPE demonstrate significant potential for extending the shelf life, enhancing safety and improving the sensory characteristics of fresh meat. Furthermore, these films